Skin-to-skin transfer from the delivery room to the neonatal unit for neonates of 1,500g or above: a feasibility and safety study - M’Rini, Meline; De Doncker, Loïc; Huet, Emilie; Rochez, Céline; Kelen, Dorottya (Frontiers in Pediatrics, 2024)
Objective: Immediate skin-to-skin contact (SSC) is already standard care for healthy term newborns, but its use for term or preterm newborns requiring admission to neonatal intensive care unit (NICU) with or without respiratory support is challenging. This study aimed to assess the safety and feasibility of SSC during the transfer of newborn infants, using a new purpose-built mobile shuttle care-station, called "Tandem".Material and methods: A monocentric prospective observational study was conducted at the tertiary referral center of the Université libre de Bruxelles in Brussels, Belgium after ethical approval by Hopital Erasme's Ethics Committee (ClinicalTrials.gov ID : NCT06198478).Infants born with a birth weight above 1500g were included. Following initial stabilization, infants were placed in SSC with one of their parents and transferred to the NICU using the Tandem.Results: Out of 65 infants initially included, 64 (98.5%) were successfully transported via SSC using the Tandem. One transfer was not successful due to last minute parental consent withdrawal. The median (range) duration of continuous skin-to-skin contact after birth was 120 minutes (10-360). SSC transfers were associated with gradually decreasing heart rate (HR) values, stable oxygen saturation levels (SpO2), and no increase in median fraction of inspired oxygen (FiO2). Heatloss was predominantly observed during initial setup of SSC. There was no significant difference in the occurrence of tachycardia, desaturation or hypothermia between preterm and term neonates. No equipment failures compromising the transfer were recorded.Conclusion: Skin-to-skin transfer of infants with a birthweight of equal or above 1500g using the Tandem shuttle is feasible and associated with stable physiological parameters. This method facilitates early bonding and satisfies parents.